Oxytocin and social anxiety: Interactions with sex hormones - Schneider, Ekaterina; Müller, Laura Elisa; Ditzen, Beate; Herpertz, Sabine; Bertsch, Katja (Psychoneuroendocrinology, 2021)
Oxytocin has been associated with anxiolytic and stress reducing effects in a number of studies. Less is known about the associations of endogenous oxytocin concentrations and their interaction with other hormones such as sex hormones in relation to self-reported anxiety levels. In this study, endogenous oxytocin and sex hormone levels were analyzed in 99 high (51 women) and 100 low (50 women) socially anxious individuals. Regression analyses showed that women with high oxytocin and estradiol levels reported a lower total Liebowitz Social Anxiety Score (LSAS) as well as a lower score on the subscale LSAS Fear. This association of hormonal interaction with social anxiety scores was significant in the subsample of high socially anxious women. In men there were no significant associations for endogenous hormones with LSAS scores. These findings suggest that in women the link between oxytocin and anxiety might be dependent on basal anxiety levels as well as on individual sex hormone levels.